Xanthogranulomatous cholecystitis or gallbladder cancer? - Ruso, Luis; Rondán, Mariela; Rodríguez, Gustavo; Mori, Raúl; Vercelli, Jorge; Balboa, Oscar (Cirugía del Uruguay, 1999)
The authors present three patients who were operated with clínica/ and imageno!ogical diagnosis of cancer of the gal/ bladder (CGB) who underwent a wide visceral resection with oncological criteria, but with patho/ogy diagnosis of xanthogranulomatous cho/ecystitis (XGC). XGC is a low incidence inflammatory disease (0,7% to 1,2%) whose main interest is differentíal diagnosis with CGB, even during surgical exploration; this is extreme/y dífficult in the presence of severe inflammatory changes